Early Left Ventricular Global Longitudinal Strain Deterioration After Aortic Aneurysm Repair: Impact of Aortic Stiffness. (April 2021) - Marketou, Maria; Papadopoulos, George; Kontopodis, Nikolaos; Patrianakos, Alexandros; Nakou, Eleni; Maragkoudakis, Spyros; Chlouverakis, Gregory; Stratakis, Stavros; Tavlas, Emmanouel; Parthenakis, Fragiskos; Ioannou, Christos V.
Purpose: To associate the impact of aortic reconstruction using currently available grafts and endografts on pulse wave velocity in patients with abdominal aortic aneurysm (AAA) and to evaluate its effect on early cardiac systolic function indices. Materials and Methods: Seventy-three consecutive patients with AAA (mean age 70±8 years; all men) who underwent open (n=12) or endovascular repair (EVAR; n=61) were prospectively enrolled in an observational cohort study. Left ventricular global longitudinal strain (GLS; an important diagnostic and prognostic index of early systolic dysfunction) and carotid-femoral pulse wave velocity (cf-PWV) were estimated 1 week preoperatively, as well as at 1 and 6 months postoperatively. Results: A significant time effect was found for cf-PWV, which showed an increase at 1 month that remained through 6 months (p=0.007). Additionally, a deterioration in GLS values was revealed, with a significant change at 1 month that persisted 6 months later (p<0.001). No significant group effect was observed between EVAR and open repair (p=0.98), and there was no significant interaction (p=0.96). Notably, the difference in GLS between baseline and 6 months significantly correlated with the corresponding changes in cf-PWV (r=0.494, p<0.001). Conclusion: AAA repair leads not only to an increase in aortic stiffness, as measured by the increase in pulse wave velocity, but also to reduced cardiac systolic function. Our findings highlight the need for a more intense cardiac surveillance program after aortic reconstruction. Further studies are needed to investigate how this may translate into long-term manifestations of cardiovascular complications and symptomatology.